Uniform approximation by incomplete polynomials - E. B. Saff; R. S. Varga (International Journal of Mathematics and Mathematical Sciences)
For any θ with 0<θ<1, it is known that, for the set of all incomplete polynomials of type θ, i.e, {p(x)=∑k=snakxk:s≥θ⋅n}, to have the Weierstrass property on [aθ,1], it is necessary that θ2≤aθ≤1. In this paper, we show that the above inequalities are essentially sufficient as well.